2019
DOI: 10.3168/jds.2018-15519
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum supplementation of fermented ammoniated condensed whey improved feed efficiency and plasma metabolite profile

Abstract: Postpartum dietary supplementation of gluconeogenic precursors may improve the plasma metabolite profile of dairy cows, reducing metabolic disorders and improving lactation performance. The objective of this trial was to examine the effects of supplementation with fermented ammoniated condensed whey (FACW) postpartum on lactation performance and on profile of plasma metabolites and hormones in transition dairy cows. Individually fed multiparous Holstein cows were blocked by calving date and randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…Prepartum energy intake of animals in this experiment was greater than maintenance to increase HYK incidence of the study population (compared to the research herd average) to be comparable to that observed in the industry. This was a part of a larger study that included a postpartum dietary intervention that reduced BHB, plasma NEFA, and improved feed efficiency [15]. The subset of cows used for this study were Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prepartum energy intake of animals in this experiment was greater than maintenance to increase HYK incidence of the study population (compared to the research herd average) to be comparable to that observed in the industry. This was a part of a larger study that included a postpartum dietary intervention that reduced BHB, plasma NEFA, and improved feed efficiency [15]. The subset of cows used for this study were Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum diets were identical except for addition of a fermented ammoniated condensed whey (FACW) supplement (GlucoBoost; Fermented Nutrition Corporation, Luxemburg, WI; Table 1) to the treatment diet. A companion paper, Caputo Oliveira et al (2019) [15], contains details on experimental design, diet formulation and chemical composition, data collection, and animal handling. For the objectives of this analysis, a subset of the cows retrospectively classified as either HYK or nonHYK were evaluated.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Weekly samples of individual feeds were dried at 55 °C in a forced-air oven for 48 h, ground to pass a 1 mm screen (Wiley Mill, Arthur H. Thomas, Philadelphia, PA, USA), and composited across each trial for nutrient composition analysis. Individual composited feeds were analyzed at a commercial lab (Dairyland Laboratories, Inc., Arcadia, WI, USA), as described previously [ 25 ]. Diet composition and nutrient analysis are presented in Supplemental Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Cows were milked twice daily at 0400 h and 1500 h. Milk yields were recorded electronically at each milking, and milk samples were taken weekly at four consecutive afternoon and morning milkings and analyzed for milk composition at a commercial laboratory (AgSource, Menominee, WI, USA), as described previously [ 25 ]. Milk samples with a composition of more than double or less than half of the next highest or lowest value for that cow, respectively, were considered biologically implausible and removed (milk fat, n = 13).…”
Section: Methodsmentioning
confidence: 99%